2021
DOI: 10.1101/2021.03.04.433933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffusion barriers and adaptive carbon uptake strategies enhance the modeled performance of the algal CO2-concentrating mechanism

Abstract: Many photosynthetic organisms enhance the performance of their CO2-fixing enzyme Rubisco by operating a CO2-concentrating mechanism (CCM). Most CCMs in eukaryotic algae supply concentrated CO2 to Rubisco in an organelle called the pyrenoid. Ongoing efforts seek to engineer an algal CCM into crops that lack a CCM to increase yields. To advance our basic understanding of the algal CCM, we develop a chloroplast-scale reaction-diffusion model to analyze the efficacy and the energy efficiency of the CCM in the gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…ROS generated in HL or conditions of nutrient deprivation may trigger changes in gene expression that are responsible for altering the pyrenoid structure and further physically isolating it from O2. A peripheral pyrenoid mesh may enhance its physical compartmentalization and create the 'cement' that holds the starch plates in place, which may allow it to serve as a more effective diffusion barrier [55][56][57] . Additionally, recent proteomic work found that proteins involved in chloroplast translation may have physical associations with the pyrenoids 54,58 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS generated in HL or conditions of nutrient deprivation may trigger changes in gene expression that are responsible for altering the pyrenoid structure and further physically isolating it from O2. A peripheral pyrenoid mesh may enhance its physical compartmentalization and create the 'cement' that holds the starch plates in place, which may allow it to serve as a more effective diffusion barrier [55][56][57] . Additionally, recent proteomic work found that proteins involved in chloroplast translation may have physical associations with the pyrenoids 54,58 .…”
Section: Discussionmentioning
confidence: 99%
“…2 ). The energetic requirement (and thus its proton gradient consumption) of the CCM depends on the inorganic carbon (C i ) availability (Fei et al ., 2021). Since the high cell concentration in the TCSPC sample leads to strong C i consumption, this could deplete the C i concentration even in the presence of bubbling, leading to a C i level sensed by cells in the TCSPC sample being lower than what is experienced by cells in the PAM sample.…”
Section: Discussionmentioning
confidence: 99%
“…The modeling did not consider additional ATP requirements for synthesis and maintenance of C i uptake complexes though, since protein accumulation and turnover rates are unknown in both native organisms and chloroplasts, which is a modest pressure onto ATP production compared to the overall daily expenditure in living cells. Recent modeling of proposed pyrenoid-based systems also highlights ATP costs to chloroplastic CCMs; however, these can be limited depending on the engineering strategy ( Fei et al, 2021 ).…”
Section: What Are the Energetic And Functional Requirements Of C I Uptake Systems?mentioning
confidence: 99%